Carbonic Anhydrase from Potato (Solanum tuberosum) Roots and Leaves - Demir, Nazan; Nadaroglu, Hayrunnisa; Demir, Yasar (Asian Journal of Chemistry, 2010)
Carbonic anhydrases (CA: carbonate hydrolase: E.C.4.2.1.1) from leaves and roots of mature potato (Solanum tuberosum) were purified and characterized. The purification levels of enzymes were 87.91 fold and 40.601 fold in leaves and roots, respectively. The optimum temperature was 40 ºC in leaves and in roots. pHs optimal were 8.5 and 11 in leaves and in roots, respectively. Enzymes of leaves were formed 5 monomers that it’s having molecular weights of 22,000, 28,000, 35,000, 40,000, 65,000, 5 polymers that it’s having 73,000, 80,000, 83,000, 132,000 and 200,000 Dalton and these proteins had carbonic anhydrase activity. But there is at the levels of 22,000, 28,000, 35,000 and 132,000 Dalton in gel filtration, for leaves. SDS-PAGE was done for roots and leaves and subunits were obtained. In addition the enzyme against the effect of NaN3, KSCN and sulphanylamide, which was known as an inhibitor of mammalian carbonic anhydrase, was determined. Potato (Solanum tuberosum) has ascorbic acid (vitamin C) in very high level and iron and calcium ions in low level. So, the effect of ascorbic acid, FeCl3 and CaCl2 in different concentrations on enzyme was determined for roots and leaves, separately. Finally, carbonic anhydrase was purified from roots and leaves of potato (Solanum tuberosum), separately and they were done optimal. Carbonic anhydrase functions in respiration and has a part in photosynthesis in plants. It was a serious deficiency that carbonic anhydrase wasn't defined in potato (Solanum tuberosum).